Activation of a Locus Coeruleus to Dorsal Hippocampus Noradrenergic Circuit Facilitates Associative Learning - Tsetsenis, Theodoros; Badyna, Julia K.; Li, Rebecca; Dani, John A. (Frontiers in Cellular Neuroscience, 2022)
Processing of contextual information during a new episodic event is crucial for learning and memory. Neuromodulation in the hippocampus and prefrontal cortex plays an important role in the formation of associations between environmental cues and an aversive experience. Noradrenergic neurons in the locus coeruleus send dense projections to both regions, but their contribution to contextual associative learning has not been established. Here, we utilize selective optogenetic and pharmacological manipulations to control noradrenergic transmission in the hippocampus during the encoding of a contextual fear memory. We find that boosting noradrenergic terminal release in the dorsal CA1 enhances the acquisition of contextual associative learning and that this effect requires local activation of β-adrenenergic receptors. Moreover, we show that increasing norepinephrine release can ameliorate contextual fear learning impairments caused by dopaminergic dysregulation in the hippocampus. Our data suggest that increasing of hippocampal noradrenergic activity can have important implications in the treatment of cognitive disorders that involve problems in contextual processing.